2007
DOI: 10.1038/sj.bjc.6603847
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) downstream signalling pathway in primary colorectal tumours and related metastatic sites: optimising EGFR-targeted treatment options

Abstract: We analysed the expression of activated (phosphorylated) Akt and MAPK in 98 cases of paired primary colorectal tumours and metastases with the aim to define better the epidermal growth factor receptor (EGFR)-related molecular profile of colorectal cancer as a tool for treatment selection. Among 47 (48%) EGFR-negative primary tumours, 35 cases (74%) were positive for phosphorylated Akt and MAPK. Among 51 (52%) EGFR-positive primary colorectal cancers, 13 (25%) cases were negative for phosphorylated Akt and 15 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
2
25
1
Order By: Relevance
“…The downregulation in metastases has recently been indicated also in other previously published studies (32)(33)(34). EGFR overexpression has been found to be associated with tumor progression and poor survival in several tumor types, such as in CRC (35), and importantly, our results underlined the involvement of NHERF1 along with EGFR in the CRC progression.…”
Section: Discussionsupporting
confidence: 87%
“…The downregulation in metastases has recently been indicated also in other previously published studies (32)(33)(34). EGFR overexpression has been found to be associated with tumor progression and poor survival in several tumor types, such as in CRC (35), and importantly, our results underlined the involvement of NHERF1 along with EGFR in the CRC progression.…”
Section: Discussionsupporting
confidence: 87%
“…However, our results indicate lower EGFR positivity in the metastases. Downregulation in metastases have recently been indicated also in other studies (20,(33)(34)(35).…”
Section: ------------------------------------------------------------supporting
confidence: 53%
“…The fraction of tumor cells being EGFR-positive varied in the range 20-95% (12,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The variations in expression of EGFR in lymph node (28,30,33) and liver metastases (29)(30)(31)(32)(33)(34)(35) were similarly high. Our values for the Hangzhou patients are in the lower part of the ranges.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Recent studies, evaluating the clinical response in patients with advanced or metastatic colorectal cancer, showed that the presence of KRAS mutation is associated with the lack of response to cetuximab [24,[33][34][35][36][37]. Patients without mutations in the KRAS gene gain therapeutic benefit from the use of cetuximab [38]. Similarly, the use of panitumumab in patients with the presence of KRAS mutations, did not bring the expected therapeutic benefit [24].…”
Section: Discussionmentioning
confidence: 99%